Outdoor Problem-Based Learning; Enhancing Critical Thinking with Real World Experiential in Science Learning - Martasari, Nurita; Supeno, Supeno; Wahyuni, Sri (FKIP Universitas Lampung, 2025)
Critical thinking is an essential thinking skill that is still a challenge for students in junior high school. This study examines the effect of a problem-based learning model outside the classroom on critical thinking skills in learning science in elementary school. The research was conducted using a quantitative approach with a quasi-experimental design. The research respondents were fourth-grade students at SDN Ditotrunan 01 Lumajang, East Java, who were divided into experimental and control groups. Students in the experimental group received problem-based learning model learning treatment outside the classroom, while students in the control group received conventional learning. The research instruments included a description test to measure critical thinking skills and an observation sheet to observe student activities during the learning process. The data were analyzed using a t-test and a gain score. The analysis showed a significant difference between critical thinking skills in the experimental and control groups. Learning with a problem-based learning model outside the classroom proved to be more effective in improving critical thinking skills than conventional learning. This study recommends using a problem-based learning model based on environmental learning resources as an alternative strategy for learning science in elementary schools.